2020
DOI: 10.1302/2633-1462.14.bjo-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders among Saudi orthopedic surgeons: a cross-sectional study

Abstract: Introduction Studies have addressed the issue of increasing prevalence of work-related musculoskeletal (MSK) pain among different occupations. However, contributing factors to MSK pain have not been fully investigated among orthopaedic surgeons. Thus, this study aimed to approximate the prevalence and predictors of MSK pain among Saudi orthopaedic surgeons working in Riyadh, Saudi Arabia. Methods A cross-sectional study using an electronic survey was conducted in Riyadh. The questionnaire was distributed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 33 publications
4
55
1
1
Order By: Relevance
“…As orthopedic surgeries are usually required to stand for long hours in the operating room, increase weight could further increase the pressure on the lower limb. Furthermore, we did not find any association between the age, years of experience, marital status, and MSK pain in our study, as conducted in other studies [2,3,6]. No clear association between smoking and MSK pain, which is different from the Al-Mohrej et al study, which suggested a susceptible relationship between smoking,back, and hip/thigh pain in comparison with non-smokers [6].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…As orthopedic surgeries are usually required to stand for long hours in the operating room, increase weight could further increase the pressure on the lower limb. Furthermore, we did not find any association between the age, years of experience, marital status, and MSK pain in our study, as conducted in other studies [2,3,6]. No clear association between smoking and MSK pain, which is different from the Al-Mohrej et al study, which suggested a susceptible relationship between smoking,back, and hip/thigh pain in comparison with non-smokers [6].…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, the effect of MSK pain (49.4%) on surgeons work was low as it affects them less than five times per week in 40and 41% doesn't take any leave due to MSK pain in the last 12 months, while 20.6 of orthopedic surgeons seek medical advice which is lower than prevalence of orthopedic surgeons in Riyadh 30% [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The total number of orthopedic surgeons in Saudi Arabia was 2,179 (Both Board certified and still under training). Out of this number, only 189 Board certified orthopedic surgeons are citizens of the capital city of Saudi Arabia, Riyadh [ 6 ]. However, the number of orthopedic residents currently under training, in Riyadh, was 191 which is our target population [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interventional cardiology, electrophysiology, vascular surgery, gastroenterology, orthopedic surgery, and neurosurgery are specialties that perform interventional procedures which frequently utilize fluoroscopy. Among these fields, physicians commonly reported WMSDs of the cervical spine and lumbar spine, which seemingly correlated with monitor viewing, wearing lead protection, poor posture, and instrument design [8][9][10][11][12][13][14][15][16][17]. The considerable increase in cervical pain among interventional cardiologists was attributed to the use of fluoroscopic monitors (P < 0.002) [9].…”
Section: Introductionmentioning
confidence: 99%